Teacher responses to racially motivated bullying in Scotland - Hay, Nicola; Davies, Elisabeth; Sapouna, Maria (Frontiers in Education, 2024)
Racially motivated bullying remains pervasive across Scottish schools. Teachers have a critical role in nurturing a safe and inclusive environment and preventing stigmatisation and oppression by intervening when a racially motivated bullying episode occurs but also by actively developing an anti-racist climate within their school by providing an anti-racism curriculum and advocating on behalf of minority ethnic youth. Despite the crucial role teachers can play in providing a safe environment, there is a paucity of literature examining the issue. While some limited research is available in England about the barriers to embedding an anti-racist curriculum, there is no research about how teachers respond to racially motivated bullying episodes, the potential barriers to responding and the processes and factors that influence teachers' judgement calls when a racially motivated bullying incident happens. Similarly, in the Scottish context there is a lacuna of knowledge about the strategies employed by teachers already within the education system and their perceptions on the support that they need to respond to racist incidents. This study aims to add to our knowledge about this issue by investigating Scottish teachers' strategies when they are confronted with a hypothetical racially motivated bullying incident in their school. Eleven interviews were conducted with a sample of teachers from different levels of education in Scotland. Teacher responses indicated a reluctance and at times, inability to recognise and name incidents as racist. Further data highlighted the reliance on strategies such as using the victim of an incident to educate their peers, one-to-one discussions with both pupils and perpetrators as well as a dependence on using their own 'instinct' to appraise an incident and response. Further sub themes emerged, including the perceived influence of generational and geospatial factors on both practitioners and the communities in which they practise and the resounding sentiment that practitioners lack engagement with anti-racist training. Our findings highlight the need to invest in schools, communities and young people in order to create the social conditions in which teachers' capacities to respond to racism can develop and flourish.